Unravelling the genome-wide contributions of specific 2-alkyl-4-quinolones and PqsE to quorum sensing in Pseudomonas aeruginosa - Rampioni, Giordano; Falcone, Marilena; Heeb, Stephan; Frangipani, Emanuela; Fletcher, Matthew P.; Dubern, Jean-Frédéric; Visca, Paolo; Leoni, Levi; Cámara, Miguel; Williams, Paul (Public Library of Science, 2016)
The pqs quorum sensing (QS) system is crucial for Pseudomonas aeruginosa virulence both in vitro and in animal models of infection and is considered an ideal target for the development of anti-virulence agents. However, the precise role played by each individual component of this complex QS circuit in the control of virulence remains to be elucidated. Key components of the pqs QS system are 2-heptyl-4-hydroxyquinoline (HHQ), 2-heptyl-3-hydroxy-4-quinolone (PQS), 2-heptyl-4-hydroxyquinoline N-oxide (HQNO), the transcriptional regulator PqsR and the PQS-effector element PqsE. To define the individual contribution of each of these components to QS-mediated regulation, transcriptomic analyses were performed and validated on engineered P. aeruginosa strains in which the biosynthesis of 2-alkyl 4-quinolones (AQs) and expression of pqsE and pqsR have been uncoupled, facilitating the identification of the genes controlled by individual pqs system components. The results obtained demonstrate that i) the PQS biosynthetic precursor HHQ triggers a PqsR-dependent positive feedback loop that leads to the increased expression of only the pqsABCDE operon, ii) PqsE is involved in the regulation of diverse genes coding for key virulence determinants and biofilm development, iii) PQS promotes AQ biosynthesis, the expression of genes involved in the iron-starvation response and virulence factor production via PqsR-dependent and PqsR-independent pathways, and iv) HQNO does not influence transcription and hence does not function as a QS signal molecule. Overall this work has facilitated identification of the specific regulons controlled by individual pqs system components and uncovered the ability of PQS to contribute to gene regulation independent of both its ability to activate PqsR and to induce the iron-starvation response.